PARENT ACTIVITIES AND STUDENT’S RETENTION IN SELECTED SECONDARY SCHOOLS IN BUKWO DISTRICT - CHEPTOYEK ISMAIL (My University, 2024)
ABSTRACT This study sought to investigate the influence of parent’s activities on student’s retention in selected schools in Bukwo District. The study objectives were; To establish the effects of Parents’ involvement in sports activities in sports activities on students’ retention in secondary schools in Bukwo district; To find the effects of parents’ advocacy for educational resources on students’ retention in secondary schools in Bukwo district; To establish the effects of school fees payment on students’ retention in secondary schools in Bukwo district. The study population was 100 respondents from the three selected secondary schools in Bukwo District. The study employed stratified random sampling techniques in coming up with a sample size of 80 respondents. The primary data collection methods used was a questionnaire was used to collect data. The collected data was analyzed using descriptive statistics in SPSS version 20. Linear and Multiple regression analysis were also used to determine the effect of the independent variables on dependent variables. The study found that Parents activity in school governance was significant in predicting student’s retention with R square value = 0.124 (0.124 *100 = 12.4%) with a p-value = 0.000<0.05. The regression coefficient of Parent’s involvement in school governance was positive and significant in predicting the student retention. Further the study found that Advocacy for educational resource had R square value = = 0. 261(0. 261*100 = 26.1%) with a p-value = 0.000<0.05. The regression coefficient of Advocacy for educational resource was positive and significant in predicting student retention. The study further found that School fees payment had significant effect in predicting student retention with p-values of 0.001 less than 0.05, R square value = = 0. 278 (0. 278*100 = 37.8%) with a p-value = 0.000<0.05.